Examining Family Cohesion and the Quality of Parent-Child Relationships Among Students with Internet Abusive Use and Normal Students - Marjan Kheirandish; Nadereh Sohrabi; Hossein Baghooli; Seyed Ebrahim Hosseini (Iranian Journal of Educational Research)
Objective: Adolescents are perpetually exposed to the perilous utilization of the Internet, which consequently engenders adverse ramifications in their adult life. The present investigation was undertaken with the objective of examining family cohesion and the quality of parent-child relationships among students exhibiting detrimental Internet usage in contrast to their normal students. Methods: The statistical population for this inquiry encompassed the students enrolled in the second year of secondary education during the academic year 2018-2019 within the educational institutions of Shiraz. The current study represents a correlational research design wherein, through the application of clean analysis methodology and predicated on the relationships among the variables, two distinct groups of students—those adversely affected by Internet usage and those deemed typical—were delineated, and subsequently, new classifications were established. In this descriptive research (causal-comparative), a sample of 120 participants (60 students exhibiting abusive Internet usage and 60 typical students) was procured through purposive sampling techniques. The participants were solicited to complete the Internet Abusive Use Questionnaire (IAUQ), the Parent-Child Relation Inventory (PCRS), and the Family Cohesion Questionnaire (FCQ). The data amassed were subjected to analysis via SPSS16. Results: The findings indicated that variables such as paternal anger, maternal role confusion, paternal communication, maternal communication, family cohesion, and the affirmative influence of mothers significantly forecast the harmful Internet usage among students. The canonical correlation of these variables in the group differentiation during clean analysis utilizing the simultaneous method was determined to be 0.959. Conclusions: The outcomes of this study substantiated the significance of family cohesion and the quality of parent-child relationships as pivotal predictors of the likelihood of harmful Internet utilization.